THEME AND RHEME OF MAIN CHARACTER SCRIPT IN HACHIKO MOVIE - Tohom Marthin Donius Pasaribu; Sumarsih Sumarsih (LINGUISTICA, 2013)
Abstract This Study Deals with the Theme and Rheme of Main Character Script in Hachiko Movie. The Objective of the study are to find out the kinds of thematic progression that is used in Hachiko movie, to find out the kinds of Theme that is used in Hachiko movie, and to find out the dominant kinds of Theme that used in Hachiko movie. This study was conducted by using descriptive design (qualitative and quantitative method). The data were collected from the script movie of Hachiko the Dog Story. The data were analyzed by the Theme and Rheme. The findings found that there were two kinds of thematic progression those are used in Hachiko movie, they were 8 constant theme patterns and 4 linear theme patterns. There were 144 (37,01%) topical themes, 151 (38,81%) interpersonal themes and 94 (24,16%) textual themes. Unmarked theme 227 (61,51%) and marked theme 142 (38,48). Interpersonal theme dominated the Hachiko movie scripts which means that the theme was the assertive or confirmation of the previous theme, because theme of the sentence has relation with the previous sentence such as expected a response from addressee or provide speaker’s comment, assessment or attitude towards the message . Unmarked theme dominated the Hachiko movie scripts which mean that the speaker utter the most typical / usual text. In the utterance the speaker put the subject and finite in front of the sentence  as the main point of the text. Keywords : Movie script, Theme